The Research on Islamic-Based Educational Leadership since 1990: An International Review of Empirical Evidence and a Future Research Agenda - Khalid Arar; Rania Sawalhi; Munube Yilmaz (Religions, 2022)
The aim of the present article was to systematically review international evidence about Islamic-based (a new term we suggest) educational leadership models published in peer-reviewed journals between 1990 and 2021. We conducted a systematic review of the literature by following the steps identified by Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). These steps were data source identification, search, data collection, eligibility criteria selection, data selection, and data analysis. They were aimed at enabling us to answer the following research inquiries: (1) What are the existing developments in research on Islamic-based educational leadership and policy? and (2) What are the main themes presented in these studies? Here, the results are presented first in a macro-outlook elucidating the main trends of this research (topical areas, geographical areas, approaches, and methods). The main themes that emerge from the analysis are: (a) policy, reforms, and stakeholders; second, educational leadership models and styles; and third, gender, feminism, and social justice. We share theoretical and methodological conclusions and outlines of some possible future research directions to contribute to inter-faith, equity, and diversity.